Reconciling value-based objectives for security and identity management. (11th June 2018) - Smith, Kane J.; Dhillon, Gurpreet; Hedström, Karin
Abstract : Purpose: In this paper, using values of individuals in a Swedish health-care organization, electronic identity management objectives related to security are defined. Design/methodology/approach: By using value-focused thinking, eliciting values from interviews of three groups of health-care staff's objective hierarchies for three stakeholder groups are identified and defined. Objective hierarchies allow comparison across multiple stakeholder groups such that strategic objectives for identity management can be compared and contrasted. Findings: This qualitative investigation, which used value-focused thinking, revealed 94 subobjectives, grouped into 12 fundamental and 14 means objectives, which are essential for developing measures that address potential value conflicts in a health-care organization around electronic identity management. The objectives developed in this study are grounded socioorganizationally and provide a way forward in developing measures aimed to reducing potential conflicts at a policy level. Originality/value: In a final synthesis, congruence (or lack thereof) in the electronic identity management approach for a Swedish health organization is suggested. This also creates a foundation to evaluate and weight different objectives for strategic decision management.